Kadar Total Asam dan Sifat Organoleptik Kefir Kombinasi Ekstrak Buah Sukun dan Susu Skim dengan Variasi Jenis Gula dan Lama Fermentasi - Firda Amanah; Titik Suryani (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
The aim of this research was to determine the total acid content and organoleptic quality of kefir combined with breadfruit extract and skim milk, with variations in the type of sugar and fermentation time. This research method uses a Completely Randomized Design (CRD) with two factors. The first factor is the variation in the type of sugar (G): granulated sugar (G1) and ant sugar (G2), and the second factor is the fermentation time (F): 36 hours (F1) and 48 hours (F2). The results of the research showed that the best total acid content in kefir combined with breadfruit extract and skim milk was found in the G1F1 treatment (30 grams of granulated sugar + 36 hours of fermentation time) of 0.76% with a pH of 3.3. The best organoleptic quality of kefir combined with breadfruit extract and skim milk is found in the G1F2 treatment (30 grams of granulated sugar + 48 hours of fermentation time) with a sour taste, white color, pleasant aroma, soft texture, and a favorable level of preference. Keywords: Type of Sugar, Total Acid Content, Kefir, Fermentation Time, Probiotic Drink, Breadfruit